Personal Hygiene pada Pasien Gangguan Jiwa di Kabupaten Polewali Mandar - Syamsidar, Syamsidar; Darmiati, Darmiati; Andriani, Ely (Mando Care Jurnal, 2024)
Mental care is a form of service to an individual in order to develop physically, mentally, spiritually, and socially so that the individual is aware of his or her abilities, can cope with stress, can work productively and can make a contribution to the community. Self-care deficit is a condition in a person who has a weakness of abilities such as being shy, unwilling to adapt to others, broken family ties, exploitation and inability to capture a lesson located in the villages of Pullipe, Tamajarra, Tamangalle, Puccadi and Leteang. In carrying out or supplementing self-care activities such as bathing (hygiene), dressing/decorating, eating, and toileting. If the patient does not do self-treatment then the consequences will be itching in the body, body smells and other diseases will develop. One of the appropriate measures for self-care deficits is to carry out self care or personal hygiene measures. The aim of this study is to provide foster care for patients with self-care deficits. The type of research method used is descriptive with a case study approach. The subject of the case study is a total of 5 (five) adults who have mental disorders self-care deficit. The conclusion from this study is that after performing personal hygiene measures in self-care deficit patients obtained patients look cleaner and can perform self-treatment independently.